2009
DOI: 10.1021/jp905887m
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Vibrational Analysis of Methyl Salicylate Isomers

Abstract: Energetics and vibrational analysis study of six isomers of methyl salicylate in their singlet ground state and first excited triple state is put forward in this work at the density functional theory level and large basis sets. The ketoB isomer is the lowest energy isomer, followed by its rotamer ketoA. For both ketoB and ketoA their enolized tautomers are found to be stable as well as their open forms that lack the internal hydrogen bond. The calculated vibrational spectra are in excellent agreement with IR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
6
24
0
Order By: Relevance
“…Therefore MD results shows that intramolecular hydrogen bonding is very slightly weakened in liquid phases but remarkable intermolecular hydrogen bonding should be discarded, and thus, interactions between neighbour molecules should be developed mainly through dipolar interactions as for its parent molecule methyl benzoate [1]. A detailed theoretical analysis of IR results for MS was previously reported by Massaro et al [9] and experimental data were reported by Varghese et al [24]. ATR-FTIR results obtained in this work are reported in Figures 3-6.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore MD results shows that intramolecular hydrogen bonding is very slightly weakened in liquid phases but remarkable intermolecular hydrogen bonding should be discarded, and thus, interactions between neighbour molecules should be developed mainly through dipolar interactions as for its parent molecule methyl benzoate [1]. A detailed theoretical analysis of IR results for MS was previously reported by Massaro et al [9] and experimental data were reported by Varghese et al [24]. ATR-FTIR results obtained in this work are reported in Figures 3-6.…”
Section: Resultsmentioning
confidence: 95%
“…Melandri et al [8] reported a rotational spectroscopy study on MS showing that the ground electronic state of this molecule adopts a form stabilized through the development of intramoleculecular hydrogen bonding between the hydroxyl and carbonyl groups. Massaro et al [9] reported a vibrational analysis of MS isomers showing that the lowest energy isomer is the MS1 form (Scheme 1), in which intramolecular hydrogen bonding between hydroxyl hydrogen and carbonyl oxygen is developed. These authors also showed that the form MS2 (Scheme 1), in which hydrogen bonding is developed between the hydroxyl hydrogen and the methoxy oxygen moieties is also very stable.…”
Section: Introductionmentioning
confidence: 99%
“…Three MS isomers (ketoB, enol, and ketoA) 23 in their gas phase were optimized within the hybrid B3PW91 scheme and basis sets 6-31++G, 6-311++G, 6-311++G(d), 6-31+G(3d,3p), and 6-311++G(3d,3p) to determine the ground state structures, force constants, and wave functions. These structures were then used as input to vertical excitation TDDFT calculations at the same level of theory.…”
Section: Structural Characteristics Of Ms Isomers In Excited Statesmentioning
confidence: 99%
“…Recently 23 we have reported the ground state energetics of six MS isomers calculated within density functional theory (DFT) and large basis sets. Notably, we have predicted that in the ground state ketoB is the most stable isomer followed in energy by the rotamer ketoA (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which these bands are excited depends on the voltage applied to, and the current flowing through, the discharge gap. Figure 7 shows [88]. The "enolized" isomers are higher energy isomers corresponding to hydrogen transfer to the ketonic oxygen.…”
Section: Discussionmentioning
confidence: 99%